"Second‐Class Status?" Insight into Communication Patterns and Common Concerns Among Men with Hereditary Breast and Ovarian Cancer Syndrome. Issue 4 (5th February 2018) - Suttman, Alexandra; Pilarski, Robert; Agnese, Doreen M.; Senter, Leigha
Abstract: Hereditary breast and ovarian cancer syndrome (HBOC) is a cancer predisposition syndrome that affects both men and women, with more significant cancer risk elevations in women. Dissemination patterns regarding familial genetic risk information among females with HBOC are fairly well defined, but knowledge about how males share this information is limited. We interviewed 21 people primarily Ashkenazi Jewish men who were accrued via listserv email through Facing Our Risk of Cancer Empowered (FORCE). Interviews focused on family cancer history, experiences with cancer and genetic testing, motivations to pursue genetic testing and subsequently disclose genetic test results, information‐sharing patterns, health care provider response, and participants' emotional support systems. The interviews were transcribed in their entirety, coded, and analyzed based on recurring themes. Eighteen transcripts were used for the analysis. Results were classified into five main themes. Participants ( n = 8) were most concerned about cancer risk for their children and female family members, and most ( n = 11) mentioned that HBOC provides them increased personal awareness, but has a negligible impact on their life overall ( n = 9). Men ( n = 11) were interested in a male‐focused support group to discuss HBOC and gain knowledge and information. Participants ( n = 9) took on active and open communication roles with family members and health care providers. The majority of participants ( n = 14) discussed the need for knowledge and awareness among the health care community and general population regarding male HBOC risks. This study serves as a pilot study and provides important and novel insights into psychosocial impacts, communication patterns, encounters with health care professionals, and expressed needs of males with HBOC.